Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/htj.21267
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on thermal performance of optimum PG brine as a radiator coolant

Abstract: The present study deals with the experimental impact of an alternative heat transfer fluids for overall performance improvement for radiators. Water and water mixed with anti‐freezing agents such as ethylene glycol (EG) and propylene glycol (PG) are the traditional coolants for an automotive radiator. Comparison of experimental and numerical analysis of optimum brine solution, that is 25% of propylene glycol and water as coolant for the rectangular fin radiator, has been well discussed. A closed loop test rig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For implementing the theoretical analysis, an engineering equation solver code is developed to study the comparative results of thermal conductivity and viscosity for Al 2 O 3 /CuO hybrid nanofluid in EG and PG binary base fluids. Thermophysical properties of EG and PG considered from at different temperatures. In‐build subroutines have been used for the temperature dependent properties of water, EG (for nanofluid also) and PG.…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…For implementing the theoretical analysis, an engineering equation solver code is developed to study the comparative results of thermal conductivity and viscosity for Al 2 O 3 /CuO hybrid nanofluid in EG and PG binary base fluids. Thermophysical properties of EG and PG considered from at different temperatures. In‐build subroutines have been used for the temperature dependent properties of water, EG (for nanofluid also) and PG.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Therefore the thermophysical study is carried out on Al 2 O 3 –CuO (50%‐50%)/water‐EG/PG at lower particle volume fraction and at a higher temperature for different shape by varying the EG/PG concentration to ensure the fluid to be used as a cooling agent. Sahoo et al investigated the application of various coolants for wavy and louvered fin radiator applications and concluded that the performance enhancement in the radiator is higher for spherical shape hybrid nanofluids compared to EG, PG brine coolants.…”
Section: Introductionmentioning
confidence: 99%
“…To experimentally study heat transfer, Yu et al [17] used a water and glycol/water mixture with a volume ratio of 40/60 or 50/50 in a specially designed and manufactured test facility that simulates the heating conditions of the coolant passage in the cylinder head area of a heavy-duty vehicle engine, and found that the heat transfer performance of the coolant decreases as the concentration of the medium increases. Sahoo et al [18] developed a new high-efficiency coolant with propylene glycol as the base fluid, used it to conduct experiments on a specially designed experimental bench, the optimum propylene glycol brine has the similar heat transfer performance as water at 80 °C.…”
Section: Introductionmentioning
confidence: 99%